AN ANALYSIS OF EURASIAN BADGER (MELES MELES) POPULATION DYNAMICS: IMPLICATIONS FOR REGULATORY MECHANISMS - Macdonald, D; Newman, C; Nouvellet, P; Buesching, C (2009)
Based on 15 years of observations of a badger (Meles meles) population at Wytham Woods in the central United Kingdom, we investigated which parameters governed demographic changes, using data recording the life histories of 868 individuals. We modeled the population in terms of a stage-classified matrix, giving an exponential population growth rate of r 0.063 (λ 1.065). Population elasticity values, derived from this matrix, produced a relative order of importance of regulatory parameters governing this population growth rate, of: adult survival (Pa) > fertility (F) > juvenile survival (Pj) > age at 1st reproduction (α) > age at last reproduction (ω). Thus, changes in Pa and F have the greatest potential to influence population growth rate. The population underwent a dramatic change in the last 5 years of the study, with a decline, then stabilization in population growth. However, this change was not related to any change in elasticity patterns between the 2 periods. Comparing the latter period to the preceding period of marked population growth revealed that fertility rate had little actual influence, whereas adult and juvenile survival rates were far more influential demographic variables. These findings prompted a 2nd, retrospective, analytical approach, a life-table response experiment (LTRE), revealing that the importance of Pj in the LTRE contrasted with its lesser prospective importance in the elasticity analysis. Change in fertility (ΔF) apparently had little environmental or genetic scope (according to the results of either technique) to influence regulation in this population. We also tested for delayed density dependence using the theta logistic model. Because territorial animals are expected to respond quickly to the effects of density dependence, corresponding to theta < 1, our rejection of this hypothesis indicated that the restrictions of territorial sociospatial regulation are relaxed in this badger population. These results are used to highlight population vulnerabilities. © 2009 American Society of Mammalogists.